Inequality growth trade-off and poverty reduction in Pakistan - Noor Fatima; Said, Rusmawati; Mazlan, Nur Syazwani; Mohamed Nor, Norashidah (Pegem Akademi Yayincilik, 2024)
This study examines the relationships between economic growth, income distribution, and poverty in Pakistan for the period 2007-08 to 2018-19. Firstly, the study estimates the sensitivity of poverty to growth and inequality at both the national and sub-regional levels. Secondly, it investigates how much growth is required to offset the negative impact of an increase in inequality on poverty in Pakistan. This trade-off between inequality and growth is computed by using a tool called the “inequality–growth trade-off index” (IGTI), employing the decomposition method proposed by Kakwani (1993). The study uses the data from the “Household Income And Expenditure Survey” (HIES) conducted by the Federal Bureau of Statistics in Pakistan. The findings indicate that ultra-poor individuals are more sensitive to changes in inequality than to changes in growth. This suggests that a greater increase in average growth is needed to offset the effects of increased inequality among the ultra-poor. Furthermore, the results suggest that poverty would decrease more significantly with a rise in average growth among the rural population compared to the urban population. In conclusion, to effectively reduce the poverty gap and the severity of poverty, policies aimed at reducing inequality would be more beneficial than those focused solely on promoting growth at the national, regional, and provincial levels in Pakistan.JEL: C14, C23, C46, I3, O52.